Evaluating the importance of collaboration among librarians - Belem, Moctar; Wan Mamat, Wan Ali; Abu Bakar, Ahmad Bakeri (IIUM Press, 2011)
With the advanced of technologies and Internet, it is become easier to be connected and collaborate with each others. In order to meet various needs of researchers and academicians, librarians must understand the strengths and effectiveness of library collaboration. Librarians' collaboration can positively improve services, satisfaction, and loyalty, and enhance relationship between institutions. This paper will discuss the importance of collaboration among librarians.